2008
DOI: 10.1348/135910707x227088
|View full text |Cite
|
Sign up to set email alerts
|

Use of mental simulations to change theory of planned behaviour variables

Abstract: Objectives The predictive validity of the theory of planned behaviour is well established, but much less is known about: (a) whether there are causal relationships between key components of the model and (b) how to go about changing the theory of planned behaviour variables. This study tested the ability of outcome and process simulations to change variables specified in the theory of planned behaviour in relation to blood donation. Design Participants (N = 146) were randomized to one of four conditions: outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 32 publications
6
38
0
Order By: Relevance
“…In contrast, process simulations involve mentally simulating the process of achieving the goal -for the person trying to lose weight, this might involve imagining signing up to exercise classes, imagining removing fatty snacks from the diet and/or imagining increasing fruit and vegetable consumption. The evidence supports the idea that process simulations are more effective than outcome simulations in changing people's behavior: Pham and Taylor (1999) showed that students who used process simulations achieved significantly higher exam grades than did students using outcome simulations, and Armitage and Reidy (2008) found that process simulations significantly increased students' motivation to donate blood in contrast with outcome simulations.…”
Section: Mental Simulationssupporting
confidence: 58%
See 1 more Smart Citation
“…In contrast, process simulations involve mentally simulating the process of achieving the goal -for the person trying to lose weight, this might involve imagining signing up to exercise classes, imagining removing fatty snacks from the diet and/or imagining increasing fruit and vegetable consumption. The evidence supports the idea that process simulations are more effective than outcome simulations in changing people's behavior: Pham and Taylor (1999) showed that students who used process simulations achieved significantly higher exam grades than did students using outcome simulations, and Armitage and Reidy (2008) found that process simulations significantly increased students' motivation to donate blood in contrast with outcome simulations.…”
Section: Mental Simulationssupporting
confidence: 58%
“…Armitage and Reidy, 2008;Pham & Taylor, 1999). Given that self-efficacy both manages anxiety in dental contexts (e.g.…”
Section: Process Simulations and Anxietymentioning
confidence: 99%
“…Armitage and Reidy (2008) did not assess planning, so the present research will contribute to previous work by examining whether the effects of health-related visualisation on intentions are mediated by planning, in addition to TPB variables such as subjective norms and perceived behavioural control (PBC), relative to a control group who do not visualise.…”
mentioning
confidence: 99%
“…These studies had participants imagine a "future exercising self" (e.g., Ouellette, Hessling, Gibbons, Reis-Bergan & Gerard, 2005), mentally contrast a desired future health goal with present reality (e.g., Johanessen, Oettingen & Mayer, 2012), or visualise implementation intentions (Knäuper, McCollam, Rosen-Brown, Lacaille, Kelso & Roseman, 2011). In addition, Armitage and Reidy (2008) showed that visualising the process of donating blood was beneficial in increasing intentions to donate blood in the future, but visualising the outcome of donating blood was not. Using the theory of planned behaviour (TPB; Ajzen, 1991) as a framework for understanding the effects of process versus outcome simulations, Armitage and Reidy demonstrated that the beneficial effects of process simulations on intentions were mediated by increased subjective norms and perceived behavioural control with respect to donating blood.…”
mentioning
confidence: 99%
“…The beneficial effect of visualizing actions from the third-person perspective holds obvious appeal for those interested in promoting health behaviors: Visualization has been shown to have reliable effects in other domains, such as sports performance (Driskell, Cooper, & Moran, 1994), and there are indications that it may be effective in motivating changes in health behavior (Armitage & Reidy, 2008;Hagger, Lonsdale, & Chatzisarantis, 2011;Ouellette, Hessling, Gibbons, Reis-Bergan, & Gerrard, 2005;Knauper, McCollam, RosenBrown, Lacaille, Kelso, & Roseman, 2011). It therefore seems possible that the use of the third-person perspective could enhance these effects.…”
mentioning
confidence: 99%